The year of the locust : a thriller - Hayes, Terry, 1951- (Emily Bestler Books/Atria, 2024)
"A Denied Access Area spy for the CIA, Kane journeys to the borders of Pakistan, Iran and Afghanistan, where violence is the only way to survive, to exfiltrate a man with vital information, but instead meets an adversary who will take the world to the brink of extinction"--